The English Curriculum Continuity and Pos Basic Learner’s Linguistic Performance in Burundi - Etienne Bikorimana; Jeanine Ntihirageza (Raja Zulkarnain Education Foundation, 2025)
Using the descriptive-correlational research design, this study examined the basic and post basic programs used to teach English in Burundi education system in order to find out the extent to which curriculum continuity is ensured across the 2 levels. Curriculum continuity was therefore assessed following Ornstein and Hunkins’ (1988) bidimensional model. The study further aimed to determine the relationship between curriculum continuity and post basic learners’ linguistic performance. In this way, two research instruments were used to collect data, mainly the document analysis and a likert scale questionnaire which was administered to a population sample of 32 learners of languages section from some selected schools in Ntahangwa communal Directorate of Education. Frequency distribution and Pearson’s r correlation were the statistical tools used to treat the data from the questionnaire while the data from document analysis were analyzed qualitatively. Findings reveal that the curriculum continuity across the two levels is ensured to a little extent. Additionally, the majority of the respondents view the continuity of curriculum at a very low level. Results further demonstrate that there is a very strong and positive relationship between curriculum continuity and learners’ linguistic performance. The study finally recommends the government of Burundi, through the Ministry of Education, to assure a smooth junction across different levels of education especially in terms of curriculum design and its implementation. Teachers are also recommended to be more creative by helping their learners be able to use the target language in and outside the classroom.